The priest's graveyard - Dekker, Ted, 1962- (New York : Center Street, 2012)
Danny Hansen is a priest who lives by a law of love and compassion. It is powerful men and hypocrites who abide by legal law but eschew the law of love that most incense Danny. As an avenging angel, he believes it is his duty to show them the error of their ways, at any cost.
Keywords: Priests -- Fiction; Vigilantes -- Fiction; Women drug addicts -- Fiction; Suspense fiction